2016
DOI: 10.1098/rsif.2016.0709
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve leaflet remodelling during pregnancy: insights into cell-mediated recovery of tissue homeostasis

Abstract: Little is known about how valvular tissues grow and remodel in response to altered loading. In this work, we used the pregnancy state to represent a non-pathological cardiac volume overload that distends the mitral valve (MV), using both extant and new experimental data and a modified form of our MV structural constitutive model. We determined that there was an initial period of permanent set-like deformation where no remodelling occurs, followed by a remodelling phase that resulted in near-complete restoratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 33 publications
5
41
0
Order By: Relevance
“…In addition to the exogenously crosslinked tissue applications addressed herein, we have observed permanent set like phenomenon in mitral valve tissue during pregnancy [45]. In that study, our results suggested that much of the growth and remodeling in the MV leaflet does not begin immediately, but rather undergoes mostly passive leaflet enlargement until these parameters reach a critically low level, at which point growth and remodeling are triggered.…”
Section: Summary and Future Directionsmentioning
confidence: 59%
See 1 more Smart Citation
“…In addition to the exogenously crosslinked tissue applications addressed herein, we have observed permanent set like phenomenon in mitral valve tissue during pregnancy [45]. In that study, our results suggested that much of the growth and remodeling in the MV leaflet does not begin immediately, but rather undergoes mostly passive leaflet enlargement until these parameters reach a critically low level, at which point growth and remodeling are triggered.…”
Section: Summary and Future Directionsmentioning
confidence: 59%
“…In addition, although the permanent set model we described only include the remodeling of the matrix due to scission-healing, the same concept can be extended by separating the rate constant into growth and resorption to simulate growth and remodeling of the matrix. Furthermore, the frame work outlined in section 5 can also be extended for the remodeling of the collagen fiber architecture, given further studies on mechanisms for how the collagen fiber architecture grows once the critical level observed in Rego et al [45] is exceeded. This is the advantage for the structural-based approach to modeling permanent set, which allows us to describe the mechanical response based on real physically measure-able quantities.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The homeostatic maintenance of MV leaflet tissue composition and microstructure, primarily mediated by interstitial cell deformation, has been shown to depend on direction‐specific loading patterns . For a physiologically relevant interpretation of strains, it is thus necessary to examine each component of the strain tensor individually.…”
Section: Methodsmentioning
confidence: 99%
“…Such alterations place the MV in a nonphysiological loading state, leading to valvular tissue growth and remodeling . In light of this, recent studies have begun to elucidate links between MV function at the organ level and the mechanobiological responses of the underlying MV interstitial cells, which ultimately drive remodeling . These investigations have uncovered and quantified detailed relationships between MV leaflet stretch and interstitial cell deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation